ANALISIS PENGARUH PENGALAMAN USAHA, DIGITAL MARKETING DAN AKSES PERMODALAN TERHADAP KINERJA UKM (Studi pada UKM di Kabupaten Buleleng Bali). - Gunawan, Ketut; Suandana, Nyoman (Universitas Panji Sakti, 2024)
The performance of SMEs in Buleleng Regency has deteriorated. This is indicated by the weakening of capital investment, declining sales volume, declining operating profits to the termination of employment (PHK). This study aims to determine various factors that influence the performance of SMEs and the most dominant influential factors. Data was collected using a questionnaire on 101 respondents as business actors. The data were analyzed by Regression analysis and Dominant analysis. The results of the analysis showed that: 1). there is an influence of Business Actor Experience on SMEs Performance; 2). There is an influence of Digital Marketing on SMEs Performance;3).There is an influence of Access to Capital on the SMEsPerformance; 4). Simultaneously, the three independent variables have a positive and significant effect on SMEs Performance; 5). Access to capital variable is the most influential factor on SMEs Performance.